PERLINDUNGAN HUKUM BAGI INVESTOR DALAM INVESTASI ILEGAL DI PLATFORM DIGITAL - Pasaribu, Joseph Kornelius; Laksana, I Gusti Ngurah Dharma (Kertha Negara : Journal Ilmu Hukum, 2025)
The purpose of this article is to analyze more in terms related to fraudulent investment activities that occur in Indonesia, to find out the regulations regarding digital investment and legal protection of investors as consumers on digital investment platforms in Indonesia territory. In writing this article, the author uses a normative legal research method, namely research based on a primary or secondary legal material approach. The results obtained by the authors in this study indicate that legal arrangements regarding investing are regulated in Law Number 25/2007 and Law Number 8/1999, but there are no specific regulations regarding digital investment. There are two forms of legal protection for investors, namely preventive and repressive legal protection, which are contained in the Civil Code, Law Number 8/1999, Law Number 21/2011, and Law Number 19/2016.